Solar Energy Potential of Building Envelopes in EMU-Campus/Famagusta for the Energy Demand by Means of Efficient PV Application - Saygı, Simge (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Climate change becomes more and more an important issue for the sustainable development of the countries. One of the reasons for the increasing climate change is the use of fossil fuels for heating, cooling, and lighting in buildings which should be replaced by renewable energy sources such as solar energy. Educational institutions play an important role in the climate change discussions. Eastern Mediterranean University (EMU) in Famagusta, which is an important educational institution in Northern Cyprus, needs a renewable energy source for the energy supply of the campus. The aim of the study is to investigate the solar energy potential of building roofs and exterior walls of the EMU campus buildings for PV application. First of all, a database about building height, floor number, roof type, vertical building surfaces areas and roof areas and their orientation as well as the obstacles which are blocking the solar radiation were established. It has been found that according to their building heights 43 out of 44 buildings in the EMU campus do not shade each other and are suitable for an efficient PV application. Hereupon, the monthly solar energy yields and the annual total solar energy yields were calculated based on the appropriate roof areas and vertical building surface areas with the help of the PVsyst Simulation program and compared with the total energy consumption in 2019. Because of the global pandemic and lockdown, the monthly and annual energy consumption of EMU in 2019 were used as statistics instead of 2020. It was found out that on a monthly basis, the calculated energy yields between October and February (Fall and Winter season) are not meeting the energy demands for the same time period. Three different scenarios were applied to increase the solar power generation between October and February (Fall and Winter season) with the same vertical building surfaces and roof areas, but with different PV tilt angles (scenario 1: 28°, scenario 2: 55°, scenario 3: 28° and 55°). The best results were achieved in scenario 3, where a flexible PV installation with a moveable tilt angle system on the total roof areas of the EMU campus was suggested as an option. On the total roof areas, the PV tilt angle 28° was applied between March and September (Spring and Summer season) and 55° between October and February (Fall and Winter season). In all scenarios (including scenario 3) the monthly solar energy yields between October and February (Fall and Winter season) generated by PVs are lower than the energy demand of the EMU campus of the same time period. Although an annual energy surplus of 68,052 kWh was achieved in scenario 3 in comparison to the EMU energy consumption in 2019. As a conclusion it can be noticed that seasonal asynchronicity between solar power generation and electricity consumption can be solved either by efficient seasonal solar power storage systems or by applying hybrid systems beside PVs. For the future development of the EMU campus, the consideration of solar energy technology must be integrated early in the design process and applied in the construction process of new smart buildings with the aim to increase the degree of selfsufficiency of the EMU campus in terms of energy use generated by fossil fuels.

ÖZ: İklim değişikliği, ülkelerin sürdürülebilir olarak kalkınması için giderek daha önemli bir konu haline gelmektedir. Artan iklim değişikliğinin nedenlerinden biri binalarda ısınma, soğutma ve aydınlatma için fosil yakıtların kullanılmasıdır. Bu tüketim güneş enerjisi gibi yenilenebilir enerji kaynakları ile değiştirilmelidir. İklim değişikliği hususunda eğitim kurumları önemli bir rol oynamaktadır. Kuzey Kıbrıs'ta önemli bir eğitim kurumu olan Gazimağusa'daki Doğu Akdeniz Üniversitesi (DAÜ), kampüsün enerji temini için yenilenebilir bir enerji kaynağına ihtiyaç duymaktadır. Çalışmanın amacı, DAÜ kampüs binalarının PV uygulaması için bina çatılarının ve dış duvarlarının güneş enerjisi potansiyelini araştırmaktır. Öncelikle bina yüksekliği, kat sayısı, çatı tipi, düşey bina yüzey alanları ve çatı alanları ve bunların yönelimleri ile güneş ışınımına mani olan engeller hakkında bir veri tabanı oluşturulmuştur. DAÜ yerleşkesinde bulunan 44 binadan 43'ünün bina yüksekliklerine göre birbirini gölgelemediği ve verimli bir PV uygulaması için uygun olduğu tespit edilmiştir. Bunun üzerine, uygun çatı alanları ve dikey bina yüzey alanları baz alınarak aylık güneş enerjisi ve yıllık toplam güneş enerjisi verimleri PVsyst Simülasyon programı yardımıyla hesaplanmıştır ve 2019 yılı toplam enerji tüketimi ile karşılaştırılmıştır. Küresel pandemi ve karantina nedeniyle 2020 yılı yerine DAÜ'nün 2019 yılındaki aylık ve yıllık enerji tüketimi istatistik olarak kullanılmıştır. Aylık olarak hesaplanan enerji verimlerinin aynı zaman dilimi içerisinde Ekim-Şubat (Güz ve Kış sezonu) enerji taleplerini karşılamadığı belirlenmiştir. Farklı PV eğim açılarıyla aynı dikey bina yüzeyleri ve çatı alanları ile Ekim ve Şubat ayları arasında (sonbahar ve kış mevsimi) güneş enerjisi üretimini artırmak için üç farklı senaryo uygulanmıştır (senaryo 1: 28°, senaryo 2: 55°, senaryo 3: 28°-55°). En iyi sonuçlar, DAÜ kampüsünün toplam çatı alanlarında hareketli bir eğim açısı sistemine sahip esnek bir PV kurulumunun bir seçenek olarak önerildiği senaryo 3'te elde edilmiştir. Toplam çatı alanlarında, Mart ve Eylül ayları arasında (ilkbahar ve yaz mevsimi) 28° ve ekim ve Şubat ayları arasında (sonbahar ve kış mevsimi) 55° PV eğim açısı uygulanmıştır. Tüm senaryolarda (senaryo 3 dahil), Ekim ve Şubat ayları (sonbahar ve kış mevsimi) arasındaki aylık Fotovoltaikler tarafından üretilen güneş enerjisi verimi, aynı zaman dilimindeki DAÜ kampüsünün enerji tüketiminden daha düşüktür. Buna ragmen Senaryo 3'te, 2019 yılında EMU enerji tüketimine kıyasla yıllık 68.052 kWh enerji fazlası elde edilmiştir. Sonuç olarak, güneş enerjisi üretimi ve elektrik tüketimi arasındaki mevsimsel eşzamansızlığın, verimli mevsimsel güneş enerjisi depolama sistemleri veya PVlerin yanında hibrit sistemler uygulanarak çözülebileceği fark edilebilir. DAÜ kampüsünün ilerideki gelişimi için, güneş enerjisi teknolojisi dikkate alınmalı, tasarım sürecinde erken entegre edilmeli ve DAÜ kampüsünün fosil yakıtların ürettiği enerji kullanımından ziyade kendi kendine yeterlilik derecesini artırmak amacıyla yeni akıllı binaların yapımı sürecinde uygulanmalıdır.
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2022. Supervisor: Assoc. Prof. Dr. Harun Sevinç
Keywords: Thesis Tez